Effects of secondary orientations on long fatigue crack growth in a single crystal superalloy. (March 2015) - Zhang, Yangyang; Qiu, Wenhui; Shi, Hui-Ji; Li, Changpeng; Kadau, Kai; Luesebrink, Oliver
Graphical abstract: Highlights: Secondary orientations strongly affect the FCG behaviors of single crystals. The energy release rate can effectively characterize the FCG behaviors. The proposed m value is capable of evaluating the FCGR of different orientations. Abstract: Fatigue crack growth (FCG) behaviors of a nickel-based single crystal superalloy were tested in 6 crystal orientations at 600 °C, and the effect of secondary orientations on FCG behaviors were investigated through theoretical analysis. FCG test results showed significant differences in FCG rates between different secondary orientations, albeit SEM observations on their fracture surfaces did not reveal evident distinctions. To evaluate the anisotropic FCG behaviors, a methodology was implemented based on the elastic energy release rate, which is successful in reducing the scatter caused by various orientations. In addition, the proposed energy release rate coefficient is proven to be effective in evaluating the resistance to long fatigue crack growth in different secondary crystal orientations.